2014
DOI: 10.1039/c4ra04690k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of acetone over CuCeOx nanofibers prepared by an electrospinning method

Abstract: A series of CuCeOx nanofiber catalysts with excellent performance toward acetone oxidation were prepared by an electrospinning method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In addition, the catalysts calcined from 400 to 700 °C possessed good stability for this reaction. 716 Following this, CuCeOx nanofiber catalysts were synthesized by Qin et al 717 using an electrospinning method. The results demonstrated that nanofiber catalysts possessed better acetone oxidation performance than catalysts prepared by the urea-nitrate oxidation and sol-gel methods.…”
Section: Acetonementioning
confidence: 99%
“…In addition, the catalysts calcined from 400 to 700 °C possessed good stability for this reaction. 716 Following this, CuCeOx nanofiber catalysts were synthesized by Qin et al 717 using an electrospinning method. The results demonstrated that nanofiber catalysts possessed better acetone oxidation performance than catalysts prepared by the urea-nitrate oxidation and sol-gel methods.…”
Section: Acetonementioning
confidence: 99%
“…No XRD patterns of Pd related species was observed in the figure, indicating a good Pd dispersion on the surface of the catalyst. The decrease in the average crystalline size with the rise in Co percent further proved the incorporation of Co ions into the CeO2 fluorite lattice because the size of the coordinated Co 2+ (0.82 Å) and Co 3+ (0.65 Å) was lower than the Ce 3+ or Ce 4+ [23,24].…”
Section: Benzene Oxidation Activitymentioning
confidence: 95%
“…The solution was stirred further for 12 h. Afterward, the resulting precursors solution was transferred into a 10 mL syringe. The spinning setup was similar to that described previously [22]. The gel precursor fibers were obtained by electrospinning; 13 kV voltage was applied to the needle, and the collection distance between the needle and collector was 15 cm.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…In another study, titanium dioxide nanofibers were fabricated via electrospinning and utilized as a support for palladium nanoparticles in the catalytic reduction of NO by CO [21]. Recently, we investigated the performance of electrospun CuCeOx nanofibers in the catalytic oxidation of acetone; the nanofiber catalysts exhibited better catalytic performance than catalysts prepared through urea-nitrate combustion and sol-gel methods [22]. Although the application of electrospun nanofibrous materials in heterogeneous catalysis has elicited some attention in recent years, further investigations have to be conducted to enhance our understanding of the catalytic properties of nanofibrous membranes.…”
Section: Introductionmentioning
confidence: 98%